2020
DOI: 10.1371/journal.pone.0236226
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of the polyamine oxidase gene family in wheat (Triticum aestivum L.) reveals involvement in temperature stress response

Abstract: Amine oxidases (AOs) including copper containing amine oxidases (CuAOs) and FADdependent polyamine oxidases (PAOs) are associated with polyamine catabolism in the peroxisome, apoplast and cytoplasm and play an essential role in growth and developmental processes and response to biotic and abiotic stresses. Here, we identified PAO genes in common wheat (Triticum aestivum), T. urartu and Aegilops tauschii and reported the genome organization, evolutionary features and expression profiles of the wheat PAO genes (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 87 publications
0
12
0
Order By: Relevance
“…The PAOs from H. vulgare ( HvPAO1 , HvPAO3 , HvPAO4 , HvPAO6 , HvPAO7 , and HvPAO8 ) are expressed systemically in all the vegetative tissues except HvPAO2 , which is expressed in sterile spikelets and embryos [ 23 , 24 ]. Similarly, the PAOs from T. aestivum ( TaPAO3 , TaPAO5 , TaPAO8 , and TaPAO11 ) are expressed systemically in vegetative tissues; however, TaPAO5 , TaPAO8 , and TaPAO11 , which are also found to be expressed in the reproductive parts [ 56 ]. The PAOs from Z. mays ( ZmPAO2 , ZmPAO3 , ZmPAO5 , ZmPAO8 , and ZmPAO9 ) are systemically expressed in all the vegetative tissues, while ZmPAO4 and ZmPAO6 are expressed specifically in roots and stems only.…”
Section: Polyamine Oxidasesmentioning
confidence: 99%
“…The PAOs from H. vulgare ( HvPAO1 , HvPAO3 , HvPAO4 , HvPAO6 , HvPAO7 , and HvPAO8 ) are expressed systemically in all the vegetative tissues except HvPAO2 , which is expressed in sterile spikelets and embryos [ 23 , 24 ]. Similarly, the PAOs from T. aestivum ( TaPAO3 , TaPAO5 , TaPAO8 , and TaPAO11 ) are expressed systemically in vegetative tissues; however, TaPAO5 , TaPAO8 , and TaPAO11 , which are also found to be expressed in the reproductive parts [ 56 ]. The PAOs from Z. mays ( ZmPAO2 , ZmPAO3 , ZmPAO5 , ZmPAO8 , and ZmPAO9 ) are systemically expressed in all the vegetative tissues, while ZmPAO4 and ZmPAO6 are expressed specifically in roots and stems only.…”
Section: Polyamine Oxidasesmentioning
confidence: 99%
“…Primary-amine oxidase (AOC3, AOC2, tynA, EC 1.4.3.21) is a heterogeneous enzyme, including copper amine oxidases (CuAOs) and flavin-containing polyamine oxidase (PAO), which catalyzes the deamination of polyamines (PAs) to amino aldehydes. It was found that copper amine oxidase (AtCuAO) in plants regulated H 2 O 2 related to abscisic acid (ABA)-induced stomatal closure [ 81 ], and participated in wound healing, defense against pathogens [ 82 ], and indole-3-acetic acid (IAA)/jasmonic acid/ABA signal transduction pathways [ 81 ], such as the closure of stomata induced by ABA [ 83 , 84 ]. In our results, we speculated that chilling-induced mobile Cmo mRNA of CuAO participated in the conversion of aminoacetone to pyruvaldehyde.…”
Section: Discussionmentioning
confidence: 99%
“…4 C). In rice, at least three PAOs ( OsPAO4/6/7 ) were induced by cold treatment, while some PAOs were invariable or even decreased under cold stress [ 58 , 59 ]. In turn, OsPAO2 and OsPAO6 were strongly induced upon oxidative stress (H 2 O 2 ) [ 58 ].…”
Section: Discussionmentioning
confidence: 99%